Philosophy-Based Learning: An Urgency in Welcoming Indonesia's Golden Generation 2045 - Hamdan Agustian; Yusuf Tri Herlambang; Yadi Suryadi; Budi Hendrawan; Rahman Wahid; Citera Yusrina (CV. Ksatria Siliwangi, 2024)
Philosophy-based learning also supports the development of character and morals in students. The aim of this study is to understand how philosophy-based learning can be integrated into the education system in Indonesia and to identify the philosophical values that are relevant for building the character of Indonesia's golden generation in 2045. The research method used is library research. The results of this study indicate that philosophy-based learning plays a crucial role in developing Indonesia's golden generation in 2045, fostering critical, reflective, and creative thinking. Despite facing various challenges, such as the cultural resistance of an education system focused on outcomes, limited teacher competencies, and the diversity of societal values, this approach remains relevant to realizing Indonesia's grand vision.